Bloodstream Infection Due to Brachyspira pilosicoli in a Patient with Multiorgan Failure - Prim, Núria (American Society for Microbiology, 2011)
Brachyspira pilosicoli is an etiological agent of human intestinal spirochetosis. Bloodstream infection due to this microorganism is rare. We report a case of B. pilosicoli bacteremia in a 70-year-old patient who presented with multiorgan failure.